A retrospective cohort study of ABO incompatible living kidney donor transplantation before and during the COVID-19 pandemic - Darren Zi Yang Lim; Terence Kee; Quan Yao Ho; Ian Tatt Liew; Carolyn Shan-Yeu Tien; Jinhua Yong; Constance Lee; Xia He; Chelsi Nicole Xin Hui Leah; Li Ting Siew; Natelie Kwan; Eleanor Ng; et al. (Proceedings of Singapore Healthcare, 2025)
Background The emergence of the Coronavirus Disease 2019 (COVID-19) Pandemic threatened living kidney donor transplantation services. Data on ABO-incompatible kidney transplants (ABOi KT) performed during the COVID-19 Pandemic is scarce. Objectives This study sought to compare characteristics and outcomes of ABOi KT performed before and during the COVID-19 Pandemic at an academic medical centre in Singapore. Methods A retrospective cohort study was performed on ABOi KT from 1 st December 2009 to 31 st May 2023. Data was compared between patients who received ABOi KT before the COVID-19 Pandemic (1 st December 2009 to 10 th March 2020 or pre-COVID-19 era) and during the COVID-19 Pandemic (11 th March 2020 to 31 st May 2023 or COVID-19 era). Results The study population consisted of 28 ABOi KT, 19 during the pre-COVID-19 era and nine during the COVID-19 era. There were no significant differences in baseline characteristics between the two groups and notably waiting time for transplantation was not significantly increased during the COVID-19 era. The median dose of Rituximab given for desensitization was low at 135 (range 0-500) mg and 100 (range 100-200) mg for both pre-COVID-19 and COVID-19 era patients. There were no significant differences in post-operative outcomes. COVID-19 infected 57.1% ( n = 16/28) of patients, among which 93.7% ( n = 15/16) were adequately vaccinated. None of these patients were admitted to the intensive care unit, died, or lost their graft from COVID-19. Conclusion Despite greater complexity and immunosuppression in ABOi KT, ABOi KT can be performed safely during the Pandemic, provided patients are adequately vaccinated and healthcare system and process are in place to minimize the risks of COVID-19.